Informatics Education in Healthcare Lessons Learned - Berner, Eta S. (Health Informatics, 2014)
This book reviews and defines the current state of the art for informatics education in medicine and health care. This field has undergone considerable change as the field of informatics itself has evolved. Twenty years ago almost the only individuals involved in health care who had even heard the term "informatics" were those who identified themselves as medical or nursing informaticians.  Today, we have a variety of subfields of informatics including not just medical and nursing informatics, but informatics applied to specific health professions (such as dental or pharmacy informatics), as well as biomedical informatics, bioinformatics and public health informatics. Informatics Education in Health Care addresses the broad range of informatics education programs available today.  The Editor and very experienced internationally recognized informatics educators who have contributed to this work have made the tacit knowledge explicit and shared some of the lessons they have learned. This book therefore represents the key reference for all involved in the informatics education whether they be trainers or trainees.